Dust production through collisions between small bodies: an application to the G-ring arc - Lattari, V. [UNESP]; Sfair, R. [UNESP]; Siqueira, P. B. [UNESP]; Schäfer, C. M. (The Royal Society, 2025)
The G-ring arc of Saturn, confined by the 7:6 corotation eccentric resonance with Mimas, is primarily composed of micrometric particles. These particles, significantly influenced by the solar radiation pressure, are subject to rapid depletion. This study investigates a mechanism for dust replenishment in the arc, specifically analysing collisions between macroscopic bodies and the satellite Aegaeon. Utilizing N-body and smoothed particle hydrodynamics simulations, we assess the dust generation from these impacts, with a focus on the most likely collision parameters derived from the N-body simulations. Our findings indicate that, while collisions among macroscopic bodies are inefficient for dust production, impacts involving Aegaeon are substantially more effective, providing conservative lower limits for dust generation. This mechanism, in conjunction with the natural decay processes and continuous dust generation from impacts, potentially keeps the arc population over thousands of years with a possible variation in brightness. This article is part of the theme issue 'Major advances in planetary sciences thanks to stellar occultations'.
Keywords: Aegaeon; dust; G-ring; numerical simulation